MAGNETIC RESONANCE IMAGING FEATURES OF INTRACRANIAL GRANULAR CELL TUMORS IN SIX DOGS. Issue 3 (25th March 2013) - Anwer, Cona C.; Vernau, Karen M.; Higgins, Robert J.; Dickinson, Peter J.; Sturges, Beverly K.; LeCouteur, Richard A.; Bentley, R. Timothy; Wisner, Erik R.
<x xml:space="preserve">Abstract</x> Magnetic resonance (MR) imaging characteristics of intracranial granular cell tumors (GCTs) have been previously reported in three dogs. The goal of this retrospective study was to examine a larger number of dogs and determine whether distinctive MR characteristics of intracranial GCTs could be identified. Six dogs with histologically confirmed intracranial GCTs and MR imaging were included. Tumor location, size, mass effect, T1‐ and T2‐weighted signal intensity, and peritumoral edema MR characteristics were recorded. In all dogs, GCTs appeared as well‐defined, extra‐axial masses with a plaque‐form, sessile distribution involving the meninges. All tumors were located along the convexity of the cerebrum, the falx cerebri, or the ventral floor of the cranial vault. All tumors were mildly hyperintense on T1‐weighted images, and iso‐ to hyperintense on T2‐weighted images. A moderate‐to‐severe degree of peritumoral edema and mass effect were evident in all dogs. Findings indicated that, while several MR imaging characteristics were consistently identified in canine cerebral GCTs, none of these characteristics were unique or distinctive for this tumor type alone.